Effect of microwave and air-borne ultrasound-assisted air drying on drying kinetics and phytochemical properties of broccoli floret. Issue 13 (1st September 2020) - Cao, Ye; Tao, Yang; Zhu, Xuhao; Han, Yongbin; Li, Dandan; Liu, Chunquan; Liao, Xiaojun; Show, Pau Loke
Abstract: The drying kinetics and detailed phytochemical profile of broccoli under microwave drying (500 and 900 W) and air-borne ultrasound (125.2 and 180.1 W/dm 2 ) assisted air drying at 70 °C were compared. The results show that, together with the faster drying speed, microwave performed better than ultrasound for the protection of chlorophylls and ascorbic acid. On the other hand, ultrasound-dried broccoli samples showed higher contents of carotenoids (lutein, zeaxanthin, α-carotene, and β-carotene), glucosinolates (glucoraphanin, glucobrassicin, and 4-methoxyglucobrassicin), and sulforaphane compared to the microwave-dried samples. The contents of lutein, glucoraphanin, glucobrassicin, and sulforaphane in the ultrasound-dried samples at 180.1 W/dm 2 were 56.5%, 13.7%, 24.9%, and 53.0% higher than that in microwave-dried samples at 900 W. Taking the aforementioned results and literature survey into consideration, it can be concluded that microwave drying has a higher drying efficiency, whereas ultrasound-assisted drying could be a better technology for the preservation of phytochemicals in fruits and vegetables.